HUBUNGAN INDEKS MASSA TUBUH DAN JUMLAH PARITAS DENGAN TIPE-TIPE KANKER ENDOMETRIUM - Yuana, Elshe; Silitonga, Hendrika A; Fauzi, Tengku Muhammad (Universitas Methodist Indonesia, 2021)
Background : Endometrial cancer is a malignant cancer in the uterine cavity in a position within the epithelial cells. Endometrial cancer has different types of cancer, namely endometrial cancer with type I (associated with estrogen) and endometrial cancer with type II (not associated with estrogen). Several trigger factors that cause endometrial cancer include parity, obesity, diabetes mellitus, history of hypertension, family genetic disease. In this study, the factors causing endometrial cancer were focused on body mass index and Total Parity to determine the relationship with the types of endometrial cancer. Methods : This research uses a literature review method. Data obtained from secondary data using documentation techniques. Data documentation is based on journals related to research variables. Results : Based on a literature review on the relationship between body mass index and types of endometrial cancer, there were journals discussing the relationship between BMI (obesity) and (normal) with Type I endometrial cancer, then journals discussing the relationship between BMI (obesity) and (obesity) and ( normal) with Type II endometrial cancer. Meanwhile, regarding the relationship between the number of parity and the types of endometrial cancer, there are journals that discuss the relationship between the number of parity (nuliparity), (primiparity) and (multipara) with Type I endometrial cancer and the number of parity (multipara) with Type II endometrial cancer. Conclusion : There is a relationship between Body Mass Index (BMI) and types of endometrial cancer. There is a correlation between the number of parity with the types of endometrial cancer